Profil Kemampuan Spasial Siswa Menengah Pertama (SMP) dalam Menyelesaikan Masalah Geometri Dimensi Tiga Ditinjau dari Kemampuan Matematika - Evi Febriana (Universitas Hamzanwadi, 2015)
Students’ difficulty within learn geomety is closely related to the spatial ability. Spatial ability is needed by students to support and solve mathematics problems, partcularly in geometry. This descriptive qualitative research aimed to describe the spatial ability of the students JHS in manipulating and rotating mentally the object and also the ability imagine the shape of object from the different perspective by giving test of geometry three dimensions. The research subjects were 3 students of JHS with different mathematical ability, namely higher level, average level, and lower level. The research subjects were given test of geometry three dimensions I and interviewed. Time triangulation was conducted to check the credibility of the data by giving test of geometry three dimensions II and interviewed again. Based on the results of analysis were found that the ability to change mentally the shape of object into different shape and the ability to move mentally the position of object were possesed by all of the subjects However, the higher and average level ability have difficulty in representing the image of three dimensions into two dimensions at the plane. Differ from those two subjects, the subject with lower level ability was found has difficulty in visualizing the shape of object from the different perspective.